2015
DOI: 10.1371/journal.pone.0135448
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of the Rubisco-Assembly Chaperone RbcX-II from Chlamydomonas reinhardtii

Abstract: The most prevalent form of the Rubisco enzyme is a complex of eight catalytic large subunits (RbcL) and eight regulatory small subunits (RbcS). Rubisco biogenesis depends on the assistance by specific molecular chaperones. The assembly chaperone RbcX stabilizes the RbcL subunits after folding by chaperonin and mediates their assembly to the RbcL8 core complex, from which RbcX is displaced by RbcS to form active holoenzyme. Two isoforms of RbcX are found in eukaryotes, RbcX-I, which is more closely related to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 41 publications
0
15
0
1
Order By: Relevance
“…RbcX is conserved from the cyanobacteria to plants (Hauser et al, 2015b ). Co-expression of the RbcX genes from various cyanobacteria as well as from C. reinhartii or A. thaliana , was shown to enhance the assembly of cyanobacterial Rubisco in E. coli (Li and Tabita, 1997 ; Onizuka et al, 2004 ; Saschenbrecker et al, 2007 ; Kolesinski et al, 2011 ; Bracher et al, 2015 ), suggesting a conserved mode of function for all the homologs. Insertional inactivation of RbcX genes that were located in or outside of the Rubisco operons in two cyanobacteria strains, suggested that the RbcX protein may be essential for Rubisco biogenesis only when it is expressed from the Rubisco operon (Li and Tabita, 1997 ; Emlyn-Jones et al, 2006 ).…”
Section: Rbcx Enhances Rbcl 8 Assembly By Stabilizmentioning
confidence: 99%
See 1 more Smart Citation
“…RbcX is conserved from the cyanobacteria to plants (Hauser et al, 2015b ). Co-expression of the RbcX genes from various cyanobacteria as well as from C. reinhartii or A. thaliana , was shown to enhance the assembly of cyanobacterial Rubisco in E. coli (Li and Tabita, 1997 ; Onizuka et al, 2004 ; Saschenbrecker et al, 2007 ; Kolesinski et al, 2011 ; Bracher et al, 2015 ), suggesting a conserved mode of function for all the homologs. Insertional inactivation of RbcX genes that were located in or outside of the Rubisco operons in two cyanobacteria strains, suggested that the RbcX protein may be essential for Rubisco biogenesis only when it is expressed from the Rubisco operon (Li and Tabita, 1997 ; Emlyn-Jones et al, 2006 ).…”
Section: Rbcx Enhances Rbcl 8 Assembly By Stabilizmentioning
confidence: 99%
“…Interestingly, Chlamydomonas encodes only the AtRbcX1 homologs, CrRbcXA and CrRbcXB. CrRbcXA was structurally and functionally characterized and shown to support cyanobacterial Rubisco assembly (Bracher et al, 2015 ). In the future, characterization of RbcX mutants as well as additional biochemical studies could reveal their precise role in Rubisco assembly and the unique properties of each homolog.…”
Section: Rbcx Enhances Rbcl 8 Assembly By Stabilizmentioning
confidence: 99%
“…Multiple chaperones have evolved to stabilize RuBisCO LS dimers during the multi-step assembly process prior to SS incorporation. In b-cyanobacteria and land plants, RbcX prevents LS aggregation by stabilizing the unstructured large subunit before being displaced by SS, although RbcX is not required for RuBisCO function in all organisms that encode it (Bracher et al, 2015;Hauser et al, 2015b). RAF1 (RuBisCO Accumulation Factor 1), found in eukaryotes and certain cyanobacteria, operates similarly to RbcX in that it also stabilizes the LS dimer before SS incorporation (Feiz et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Three assembly factors have been identified for green-type Rubisco; RbcX, Rubisco accumulation factor 1 (Raf1), and Raf2 (Bracher et al, 2015;Feiz et al, 2014;Feiz et al, 2012;Hauser et al, 2015a;Kolesinski et al, 2014;Li et al, 1997;Liu et al, 2010 interacts with RbcL downstream of chaperonin-associated RbcL folding. They function to stabilized RbcL2 but bind using different interaction sites (Bracher et al, 2017).…”
Section: Biogenesis and Assembly Of Form I Rubiscomentioning
confidence: 99%